Hybrid Electric Power Plant Using Wind Turbine Savonius Helix and Solar Cell as an Alternative Power Source in the Lightning Tower at Flashing Lights - Suryadi, Aris; Asmoro, Purwandito Tulus; Solihin, Ahmad (ADI Publisher, 2019)
Electrical Energy is a very important need, but the electrical energy we use today still comes from conventional power plants that have negative threats such as pollution and fossil fuel reserves that are decreasing. To overcome this, by utilizing alternative energy that is environmentally friendly, one of them is wind energy and solar energy. Hybrid power plants use savonius helix wind turbines and solar cells are made to minimize the use of conventional energy. This tool utilizes wind and solar energy as the main media of electricity generation. The wind turbine which is made is a type of helix savonius vertical turbine that has a large torque, can rotate with low wind speed with a turbine size 80 cm high, diameter 25 cm which is connected to the generator and mounted on mechanical construction with a height of 200 cm and mounted control panel and solar cell with a capacity of 20 WP. This study aims to develop the potential of alternative energy as a power generation medium and be used as a source of flashing lights in the Indorama Engineering Polytechnic lightning tower tower. Savonius helix wind turbines that are designed require a minimum wind speed of 2.45 m / s for the start of the turbine rotation. Generating from the generator produces a maximum voltage of 18.64 V with a generator rotation of 304 rpm when not loaded and when loaded produces a maximum spin voltage of 281.3 rpm, 11.73 V voltage and 0.038 W power with a wind speed of 5 m/s. From the results of testing this hybrid power plant can be used for flashing lights on the lightning rod tower of the Indorama Polytechnic Engineering campus with a duration of 12 hours per day